Low-loss shielded through-silicon vias filled with multi-walled carbon nanotube bundle. (December 2016) - Su, Jinrong; Ma, Runbo; Chen, Xinwei; Han, Liping; Yang, Rongcao; Zhang, Wenmei
Abstract: In this paper, the multi-walled carbon nanotube bundle (MWCNTB) based shielded through-silicon via (S-TSV) is proposed and the compact expression for the equivalent conductivity of MWCNTB ( σ MWCNTB ) is deduced to calculate the resistance of MWCNTB based S-TSV (MS-TSV). Then, the electrical characteristics including the S parameters, attenuation constant and time delay are investigated. The results indicate that | S 21 | of MS-TSV increases with the increase of the outermost diameter of MWCNT and decrease of the thickness of the shielding layer. Compared with the copper filled S-TSV (CuS-TSV), the MS-TSV has a larger | S 21 |, smaller attenuation and shorter time delay. Finally, the impact of the geometrical parameters on the conductivity of MS-TSV is analyzed. Also, the minimum packing density of MWCNTB satisfying σ MWCNTB ≥ σ Cu has been deduced. The results show that the outermost diameter of MWCNT has the most significant impact on the conductivity of MS-TSV, and thicker MWCNT is helpful to increase the conductivity of MS-TSV, decrease the packing density of MWCNTB and reduce manufacturing difficulty.